The Art of Hosting Participatory Practices in Social Labs: Moving Beyond Participation to Deep Engagement : A case study of the Economic Immigration Lab in New Brunswick, Canada - Mosse, Rosamund; Muirhead, Lewis (FormAkademisk, 2020)
Working with diverse groups to address complex issues is the primary aim of the burgeoning field of social labs. This paper investigates how the Art of Hosting (AoH) helped the facilitation team at New Brunswick’s Social and Public Innovation Lab (NouLAB) to build trust and integrate the wisdom of the participants into the lab process. We argue that AoH provided a container for the deep understanding and changes in perspective experienced by participants in the first two cycles of the lab. This study may be of use to those planning multi-stakeholder engagements and working in complex problem spaces. Keywords: Social innovation labs, Art of Hosting, participatory practices, public sector innovation, dialogic organizational development.